Exploring the Dark Side of Tax Policy: An Analysis of the Interactions between Fiscal Illusion and the Shadow Economy - Andreas Buehn; Roberto Dell' Anno; Friedrich Schneider (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper presents an empirical analysis of the relationship between fiscal illusion and the shadow economy for 104 countries over the period 1989–2009. We argue that both unobservable phenomena are closely linked to each other, as the creation of a fiscal illusion may be helpful if governments want to control shadow economic activities. Using a MIMIC model with two latent variables we confirm previous findings on the driving forces of the shadow economy and identify the main determinants and indicators of fiscal illusion. Most importantly, we find that fiscal illusion negatively affects the shadow economy and the shadow economy positively affects fiscal illusion. Concealing the real tax burden we find that an increase of taxation increases both shadow economic activities and fiscal illusion.
Keywords: O17; K42; E62; 330; fiscal illusion; shadow economy; MIMIC model; latent variables; tax burden; tax complexity